2019
DOI: 10.1021/acsomega.9b01245
|View full text |Cite
|
Sign up to set email alerts
|

Planar Heterojunction Solar Cell Employing a Single-Source Precursor Solution-Processed Sb2S3 Thin Film as the Light Absorber

Abstract: We discuss here a solution-processed thin film of antimony trisulphide (Sb 2 S 3 ; band gap ≈ 1.7 eV; electronic configuration: ns 2 np 0 ) for applications in planar heterojunction (PHJ) solar cells. An alternative solution processing method involving a single-metal organic precursor, viz., metal–butyldithiocarbamic acid complex, is used to grow the thin films of Sb 2 S 3 .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…15,16 In contrast, the carrier transport along the direction is much more efficient because it is governed by intraribbon carrier transport with a reduced recombination probability. 18 Indeed, Roy et al, by studying the electric and magnetic properties of a single Sb 2 S 3 crystal, confirmed that the conductivity along the [hk1] direction was almost 2 orders of magnitude higher than that along the [hk0] direction. 19 In addition, the surfaces orthogonal to the [hk1] orientation usually have the lowest surface energies and no dangling bonds, thereby reducing the surface trap sites in the Sb 2 S 3 film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 In contrast, the carrier transport along the direction is much more efficient because it is governed by intraribbon carrier transport with a reduced recombination probability. 18 Indeed, Roy et al, by studying the electric and magnetic properties of a single Sb 2 S 3 crystal, confirmed that the conductivity along the [hk1] direction was almost 2 orders of magnitude higher than that along the [hk0] direction. 19 In addition, the surfaces orthogonal to the [hk1] orientation usually have the lowest surface energies and no dangling bonds, thereby reducing the surface trap sites in the Sb 2 S 3 film.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its unique quasi-1D crystal structure, the optoelectronic properties of Sb 2 S 3 strongly depend on its crystallographic orientation. , The orthorhombic Sb 2 S 3 has a two-dimensional layered structure composed of infinite (Sb 4 S 6 ) n chains (ribbons) along the c axis through S–Sb covalent bonds, which are linked by weak van der Waals (vdWs) interaction along the b axis. This quasi-1D crystal structure of Sb 2 S 3 is responsible for its direction-dependent carrier transport property. The carrier transport along the [ hk 0] direction is inefficient because the carrier transport mechanism along this direction is interchain or interlayer hopping. , In contrast, the carrier transport along the [ hk 1] direction is much more efficient because it is governed by intraribbon carrier transport with a reduced recombination probability . Indeed, Roy et al, by studying the electric and magnetic properties of a single Sb 2 S 3 crystal, confirmed that the conductivity along the [ hk 1] direction was almost 2 orders of magnitude higher than that along the [ hk 0] direction .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The nontoxicity and earth-abundance of its constituents make Sb 2 (S,Se) 3 a promising candidate to compete with existing materials for commercial photovoltaics. [7] Moreover, Sb 2 (S,Se) 3 has a stable single orthorhombic phase with a Q1D crystal structure (Figure S1, Supporting Information), [8,9] resulting in anisotropic electrical properties in the film. [10] It has been reported that conductivity along the (Sb 4 X 6 ) n (X = S or Se) ribbons (c-axis) is much higher than the other directions that require electron hopping between adjacent ribbons.…”
Section: Introductionmentioning
confidence: 99%
“…But from 10 3 Ω to 10 7 Ω there is no change in 𝐽 𝑆𝐶 . The Fill Factor has been increased from 25.0271% to 73.2517% with the increase in shunt resistance [27]- [30]. The conversion efficiency has increased from 10Ω to 10 6 Ω, but after 10 6 Ω, efficiency tends to be constantly shown in Fig.…”
Section: Effect Of Shunt Resistance On Photovoltaic Parameters Of Sb2...mentioning
confidence: 93%